Komunikasi Interpersonal dalam Organisasi Pemuda Muhammadiyah Kecamatan Tombolopao Kabupaten Gowa - Habriadi (Danudirja Setyabudi Nusantara, 2025)
This study examines the success of interpersonal communication in the Muhammadiyah Youth Organisation Branch in Erelembang Village, Gowa Regency. The study uses a descriptive qualitative approach with in-depth interviews with 12 informants, direct observation, and document analysis during September-November 2024. The results of the study found four methods of interpersonal communication that were applied: (1) repetition of messages that took advantage of close relationships in rural areas; (2) persuasion through two-way dialogue; (3) delivery of information with clear evidence of the benefits of organizing; and (4) a firm approach limited to members with specific characteristics. The success of communication was measured using five indicators that showed the creation of openness, mutual understanding, support, favorable responses, and equality in communication. The findings show that interpersonal communication is more successful than group communication in rural environments, with persuasion having the best impact. The contribution of this research lies in the development of an organisational communication model suitable for rural areas and an understanding of how to adapt communication methods to local characteristics.